Natural regeneration of Alnus spp. (alder) in the Pusqui and Dos de Mayo annexes, Tayacaja - Huancavelica - Aquino Victoria, Jhonatan Alberto (2024)
The success of forest management depends to a large extent on the availability of sufficient resources, so natural regeneration ensures the sustainability of resources over time, which is very important to create knowledge or scientific basis in relation to forest dynamics. For this reason, the research was developed with the aim of evaluating the natural regeneration of Alnus spp. (alder) and the relationship of the requirements of the aforementioned species with the environmental factors of the Pusqui and Dos de Mayo annexes, in the province of Tayacaja, Huancavelica region. The research area consisted of 146 individuals of natural regeneration between seedlings, saplings, low latizales and high latizales, of which 84 individuals were reported in the Dos de Mayo annex and 62 individuals in the Pusqui annex. The most abundant natural regeneration category in the two annexes was the low latizal category with 47,3%, followed by the sapling category with 31,5%, followed by the seedling category with 19,9% and finally by the high latizal category with 1,4%. The soil and climatic factors of both annexes coincide with the soil and climatic requirements of Alnus spp. (alder), especially in the values of pH, precipitation and relative humidity.